1995
DOI: 10.1159/000217953
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Immune Changes in Patients with Renal Cancer and Melanoma Treated with Interferon-&alpha;<sub>2b</sub>

Abstract: We evaluated the response rate and the immunorestorative properties of subcutaneously administered in-terferon-α2b (IFN- α2b ) in patients with advanced renal cell carcinoma (RCC) and melanoma (MEL) and correlated the immune status with clinical responses. Thirty-five patients with advanced RCC and 12 with MEL were treated with re-combinant IFN- α2b The dose was increased progressively from 5 × 106 IU the first week to 10 × 106 IU the second week and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…We have previously demonstrated that localisation of CD4 þ , CD8 þ and CD57 þ lymphocytes to sites of tumour is a requisite for the response to therapy (Donskov et al, 2002a), thus hypothesising that the antitumour activity of IFN-a in vivo is primarily cellular immune mediated. This hypothesis is in accordance with previous in vitro findings (Kosmidis et al, 1992;Tsavaris et al, 1996).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We have previously demonstrated that localisation of CD4 þ , CD8 þ and CD57 þ lymphocytes to sites of tumour is a requisite for the response to therapy (Donskov et al, 2002a), thus hypothesising that the antitumour activity of IFN-a in vivo is primarily cellular immune mediated. This hypothesis is in accordance with previous in vitro findings (Kosmidis et al, 1992;Tsavaris et al, 1996).…”
Section: Discussionsupporting
confidence: 94%
“…Whereas cellular immune effector mechanisms are considered to be the most important mediators of IL-2 antitumour activity (Rubin et al, 1989;Donskov et al, 2002a), IFN-a in addition (Kosmidis et al, 1992;Tsavaris et al, 1996;Donskov et al, 2002a) is considered to exert antiproliferative (Grander et al, 1997) and differentiationinducing effects on the tumour cells (Pfeffer et al, 1998). In vitro, a direct antiproliferative effect on renal tumour cells has been demonstrated for IFN-a (Nanus et al, 1990), whereas IL-2 has no direct impact on cancer cells (Rosenberg, 2001).…”
mentioning
confidence: 99%
“…Moreover, an important aspect of the present study was that baseline pretreatment measurements of IL-2, IFN-g, and GM-CSF serum levels, as well as NK and LAK cell cytotoxicity were depressed in patients (either in the paclitaxel or docetaxel group) compared to healthy normal blood donors, indicating impaired immunity at the start of treatment, a finding that is consistent to those regarding other tumour types investigated by our group in the past, such as colon cancer, melanoma and renal -cell carcinoma. For instance, most patients with colon cancer had impaired immunological parameter values after surgery, before the start of treatment and these returned to normal or surpassed it after responding to immunotherapeutic manoeuvres (Tsavaris et al, 1996;Baxevanis et al, 1997). In contrast, IL-6 serum levels were increased in our breast cancer patients at baseline, compared to normal controls and raised further significantly after treatment with both taxanes, a finding that might point to a direct effect of taxanes on hepatocytes or enhancement of tumour-induced Th2-directed inflammatory reaction.…”
Section: Clinicalmentioning
confidence: 99%
“…Of 12 melanoma patients, four patients showed a partial response whereas eight patients progressed. 109 In the case of 35 patients with advanced renal cancer, an increase in immune response potential was observed. 109 The conclusion was that more studies are required to determine the therapeutic effectiveness of INFa 2b .…”
Section: Interferon-a 2bmentioning
confidence: 99%